A study to establish factors that lead to non adherence to anti-retroviral treatment for orphans living with HIV in Okahandja Constituency - Mumbuna, Yetambuyu (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2011.